Soluble urokinase‐type plasminogen activator receptor as a putative marker of male accessory gland inflammation. (18th September 2015) - Autilio, C.; Morelli, R.; Milardi, D.; Grande, G.; Marana, R.; Pontecorvi, A.; Zuppi, C.; Baroni, S.
Summary: The association between male accessory gland infection/inflammation (MAGI) and infertility is well‐known in clinical practice. Standard semen analysis, leukocytospermia, and microbiological tests are often not enough accurate for a diagnosis. A large amount of biochemical parameters in seminal plasma have been suggested as inflammation markers, however, there is not yet a sensitive and specific biomarker that accurately identifies MAGI. We investigated the presence of soluble urokinase‐type plasminogen activator receptor (suPAR), known marker of systemic inflammation, in the seminal plasma to evaluate its possible involvement in urogenital tract inflammation. On the basis of andrological evaluation, including spermiogram and ultrasound findings, we selected 76 patients with MAGI and 30 healthy men as control group. Patients were classified according to the results of the semen culture in group A ( n  = 28) presenting a bacterial MAGI and group B ( n  = 48) with abacterial MAGI. C‐reactive protein (CRP), total protein (TP), procalcitonin (PCT), leukocytes peroxidase (LP), and suPAR concentrations were assayed on seminal plasma. Spermiogram parameters were significantly lower in the patients with MAGI than in controls. CRP, TP, PCT, and LP did not differ in MAGI vs. controls. suPAR was detectable in all semen samples; it was significantly increased in A and B groups (86.6 ± 30.7 ng/mL vs. 39.7 ± 17.2 ng/mL) with an inverse correlation with sperm parameters. We selected by receiver operating characteristic curve a suPAR cut‐off value of 55.3 ng/mL as a diagnostic threshold for the diagnosis of MAGI. We report in this study the first evidence of suPAR presence in seminal plasma, focusing on its interesting role as reliable and sensitive marker of inflammation for the differential diagnosis of MAGI.